2000
DOI: 10.1302/0301-620x.82b7.0821077
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound accelerates bone maturation in distraction osteogenesis in rabbits

Abstract: We investigated the effects of low-intensity pulsed ultrasound on distraction osteogenesis in a rabbit model.Callotasis of the right tibia was performed in 70 male Japanese white rabbits using mini-external fixators. In the first part of the study in 64 animals using normal distraction (waiting period seven days; distraction rate 0.5 mm/12 hours; distraction period ten days), we evaluated the distraction site by radiography, measurement of the bone mineral density (BMD), mechanical testing, and histology. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 10 publications
0
58
1
4
Order By: Relevance
“…Wolff law indicates that bone structures are reconstructed by the outside force and its direction and the physiological response and healing process are influenced by mechanics. Also ultrasound can improve the local blood flow, speed up the transportation of growth factor and cytokines available for the healing of bone fracture [4] . Studies revealed that the effects of ultrasound on the healing process of bone fracture might be contributed to the following biological mechanisms: Ultrasound induces the changes in cell membrane, resulting in the changes in ion permeability and the activation of second message, which in turn leads to the changes in gene expression and further up-regulates the expression of cartilage and bone specific genes [3] , so accelerating the healing of bone fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Wolff law indicates that bone structures are reconstructed by the outside force and its direction and the physiological response and healing process are influenced by mechanics. Also ultrasound can improve the local blood flow, speed up the transportation of growth factor and cytokines available for the healing of bone fracture [4] . Studies revealed that the effects of ultrasound on the healing process of bone fracture might be contributed to the following biological mechanisms: Ultrasound induces the changes in cell membrane, resulting in the changes in ion permeability and the activation of second message, which in turn leads to the changes in gene expression and further up-regulates the expression of cartilage and bone specific genes [3] , so accelerating the healing of bone fracture.…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS has been widely found to stimulate fracture healing in animal models and in clinical treatments [4, 5]. LIPUS has also been reported to accelerate bone maturation in distraction osteogenesis cases in animal models [6, 7] and in clinical treatments [8, 9]. LIPUS may induce a micromechanical stimulation of the bone and induce osteogenesis, according to Wolff's Law [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has therapeutic potential; in vivo animal studies demonstrated that LIUS accelerated the healing of bone fractures. LIUS enhances the mechanical properties of the healing callus,7–9 as well as bone bridging,9, 10 and is also effective for treating nonunion fractures11, 12 and distraction osteogenesis in animal models and clinical trials 13, 14. Ultrasound appears to affect healing by modulating bone structure.…”
mentioning
confidence: 99%